Is Single-stage Revision According to a Strict Protocol Effective in Treatment of Chronic Knee Arthroplasty Infections? - Haddad, Fares Sami (Clin Orthop Relat Res, 2014)
BACKGROUND: The increasing number of patients experiencing periprosthetic total knee arthroplasty (TKA) infections and the cost of treating them suggest that we seek alternatives to two-stage revision. Single-stage revision is a potential alternative to the standard two-stage procedure because it involves only one surgical procedure, so if it is comparably effective, it would be associated with less patient morbidity and lower cost. QUESTIONS/PURPOSES: We compared (1) the degree to which our protocol of a highly selective single-stage revision approach achieved infection control compared with a two-stage revision approach to TKA infections; and (2) Knee Society scores and radiographic evidence of implant fixation between the single-stage and two-stage patients who were treated for more complicated infections. METHODS: Between 2004 and 2009, we treated 102 patients for chronic TKA infections, of whom 28 (27%) were treated using a single-stage approach and 74 (73%) were treated using a two-stage approach. All patients were available for followup at a minimum of 3 years (mean, 6.5 years; range, 3–9 years). The indications for using a single-stage approach were minimal/moderate bone loss, the absence of immunocompromise, healthy soft tissues, and a known organism with known sensitivities for which appropriate antibiotics are available. Participants included 38 men and 64 women with a mean age of 65 years (range, 45–87 years). We used the Musculoskeletal Infection Society definition of periprosthetic joint infection to confirm infection control at the last followup appointment. Radiographs were evaluated for signs of loosening, and patients completed Knee Society Scores for clinical evaluation. RESULTS: None of the patients in the single-stage revision group developed recurrence of infection, and five patients (93%) in the two-stage revision group developed reinfection (p = 0.16). Patients treated with a single-stage approach had higher Knee Society scores than did patients treated with the two-stage approach (88 versus 76, p < 0.001). However, radiographic findings showed a well-fixed prosthesis in all patients with no evidence of loosening at last followup in either group. CONCLUSIONS: Our data provide preliminary support to the use of a single-stage approach in highly selected patients with chronically infected TKAs as an alternative to a two-stage procedure. However, larger, multicenter, prospective trials are called for to validate our findings. LEVEL OF EVIDENCE: Level III, therapeutic study. See Instructions for Authors for a complete description of levels of evidence.